Transcriptome profiling of high and low somatic embryogenesis rate of oil palm (Elaeis guineensis Jacq. var. Tenera) - Sahara, Asri; Roberdi, Roberdi; Wiendi, Ni Made Armini; Liwang, Tony (Frontiers in Plant Science, 2023)
Oil palm micropropagation through tissue culture is a technique to provide elite oil palms to meet the desired traits. This technique is commonly carried out through somatic embryogenesis. However, the oil palm’s somatic embryogenesis rate is quite low. Several approaches have been made to overcome this problem, including transcriptome profiling through RNA-seq to identify key genes involved in oil palm somatic embryogenesis. RNA sequencing was applied in high and low embryogenic ortet of Tenera varieties based on the somatic embryoid rate at the callus, globular, scutellar, and coleoptilar embryoid stages. Cellular analysis of embryoid inductions and proliferations showed that high embryogenic ortets resulted in higher embryoid proliferations and germinations than low embryogenic ortets. Transcriptome profiling showed that in total 1,911 genes were differentially expressed (DEGs) between high and low embryogenic ortets. ABA signaling-related genes such as LEA, DDX28, and vicilin-like protein are upregulated in high embryogenic ortets. Furthermore, DEGs associated with other hormone signaling, such as HD-ZIP associated with brassinosteroids and NPF associated with auxin, are upregulated in high embryogenic ortet. This result suggests a physiological difference between high and low embryogenic ortet that is connected to their capacity for somatic embryogenesis. These DEGs will be used as potential biomarkers for high embryogenic ortet and will be validated for further studies.